Improving efficiency indicators and reducing CO2 emissions by using hydrogen and methane additives to gasoline in a spark-ignition engine - Marchenko, Andrii; Mishchenko, Mykyta (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates the working process in a 4Ch7.6/6.6 gasoline engine when using hydrogen and methane additives to fuel. The task addressed relates to the lack of a single methodological approach to the comparative quantitative assessment of the impact of various gas additives on combustion parameters, efficiency indicators, and CO2 emissions. As a result, there is a complication of the justified choice of the optimal component to increase energy efficiency and reduce the carbon footprint of the existing fleet of gasoline engines. This work advanced semi-empirical relationships for determining the parameters of the Wiebe model when methane is added to gasoline, which are based on scaling through the ratio of laminar flame velocities. Based on the results from mathematical modeling, it was established that when adding 10% hydrogen, the combustion dynamics indicator m decreases by 32.4–38.7% while the combustion duration φz is reduced by 26.1–28.2%. It was determined that the specific effective fuel consumption decreases by 13.9–14.3%, the effective efficiency increases by 0.5–1.8%, and the volume fraction of CO2 decreases by 14.1%. When methane is added to 10%, the dynamics parameter m increases by 3.2–3.9%, and, accordingly, the combustion duration φz increases by 2.4–2.6%, while the specific consumption decreases by 2.3–4.8%, the effective efficiency increases by 1.4–3.7%, and a decrease in CO2 is also observed, which is 11.7%. A defining feature is the quantitative results of the effect at the same proportion of the additive (10%), according to which hydrogen provides a 1.2-fold greater reduction in CO2 compared to methane, but at the same time an improvement in fuel efficiency is observed. The results allow for a reasonable choice of the type of additive for a comprehensive increase in efficiency and environmental friendliness or moderate decarbonization at minimal engine modernization